In utero exposure to hexavalent chromium disrupts rat fetal testis development. (15th December 2018) - Zheng, Wenwen; Ge, Fei; Wu, Keyang; Chen, Xianwu; Li, Xiaoheng; Chen, Yong; Lv, Yao; Lian, Qingquan; Ge, Ren-Shan
Graphical abstract: Highlights: Chromium has biphasic effects on fetal Leydig cell function. Chromium upregulates fetal Leydig cell gene expression at low dose. Chromium downregulates fetal Leydig cell gene expression at high dose. Chromium increases single fetal Leydig cell population at high dose. Abstract: Hexavalent chromium (Cr 6+ ) acts as an endocrine disruptor. Herein, we investigated effects of Cr 6+ on the development of rat fetal Leydig and Sertoli cells, which support differentiation of the male reproductive tract in late gestation. Female pregnant Sprague Dawley rats were gavaged with potassium dichromate (0, 3, 6, and 12 mg/kg) from gestational days (GD) 12 to GD 21. Leydig and Sertoli cell function was evaluated by investigating serum testosterone levels, cell number and distribution, and the expression levels of Leydig and Sertoli cell genes and proteins. Cr 6+ increased serum testosterone level at dose of 3 mg/kg (1.170 ± 0.121 ng/ml vs. 0.720 ± 0.082 ng/ml in the control), while lowered it at dose of 12 mg/kg (0.400 ± 0.098 ng/ml). In addition, it showed that Cr 6+ dose-dependently reduced Leydig cell size and cytoplasmic size and decreased the percentage of medium fetal Leydig cell cluster at dose of 12 mg/kg. Further study demonstrated that the expression of Leydig cell ( Lhcgr, Scarb1, and Hsd3b1 ) and Sertoli cell ( Fshr, Pdgfa, and Lif ) genes in the testis was upregulated at dose of 3 mg/kg while the expression of Lhcgr, Hsd17b3 and Igf1 was downregulated by Cr 6+ at dose of 12 mg/kg. In conclusion, Cr 6+ had biphasic effects on fetal Leydig cell development with low dose to stimulate testosterone production and high dose to inhibit it, possibly via biphasically regulating growth factor gene expression in fetal Sertoli cells.